Implementasi Sistem PLTS untuk Kebutuhan Listrik Pelaku Usaha Ternak Ikan Toman Rahayu - Yuniarta Basani; Yunus Pebriyanto; Decenly Decenly (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
Limited access to electricity remains a major challenge for fisheries enterprises located in remote areas, including Ternak Ikan Toman Rahayu, which operates floating cages along the Pager River in Palangka Raya. This condition reduces operational efficiency and productivity due to the absence of a reliable power supply. Therefore, this community service program aimed to implement an off-grid Solar Power System (PLTS) as a sustainable and independent energy solution. The implementation method consisted of field observation and needs assessment, installation of the off-grid PLTS, training on system operation and maintenance, and evaluation through in-depth interviews. The results indicate that the implemented PLTS successfully provides a stable electricity supply for lighting and work equipment, while also enhancing the partner’s knowledge and independence in managing renewable energy systems. The off-grid PLTS implementation effectively supports business sustainability and promotes the utilization of renewable energy within the community.